Antimicorbial Potency of Major Functional Foods’ Essential Oils in Liquid and Vapor Phases: A Short Review - Azam Amiri; Javad Mottaghipisheh; Fatemeh Jamshidi-Kia; Karamatollah Saeidi; Sara Vitalini; Marcello Iriti (Applied Sciences, 2020)
Due to the increasing risk of chemical contaminations in the application of synthetic fungicides, the use of plant essential oils and extracts has recently been increased. In the present review, the antimicrobial potential of the most active plant-food essential oils in liquid and vapor phases has been reviewed. The volatile isothiocyanates, aldehydes, and phenols, including allyl isothiocyanate, carvacrol, thymol, and eugenol, are considered to be the predominant components of essential oils, possessing significant antimicrobial activities. These components alone or in mixture can be effective. Overall, the antimicrobial activity of aroma compounds depends on the plant species, concentration, and method of application. This review provides useful information about the inhibitory application of the most common plant-foods’ essential oils in liquid and vapor phases against the growth of pathogenic microorganisms. Essential oils (EOs) are promising natural antimicrobial alternatives in food processing facilities. Although the food industry primarily uses spices and herbs to impart flavor, aroma, and pungency to foods, potent EOs represent interesting sources of natural products for food preservation.